Research of the object-oriented programming learning environment - Lipeikienė, Joana; Kalpaitė, Kristina; Kluonytė, Aušra (Lietuvos matematikos rinkinys, 2002)
Research and results of the use of C++ Learning Environment for teaching at Vilnius Pedagogical University are described in this paper. Results of questionnaires and Web Ct statistical data were used for the research.